2013
DOI: 10.1371/journal.pone.0067607
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Glycoprotein 130 Family of Cytokines in Fetal Rat Lung Development

Abstract: The glycoprotein 130 (gp130) dependent family of cytokines comprises interleukin-6 (IL-6), IL-11, leukemia inhibitory factor (LIF), cardiotrophin-like cytokine (CLC), ciliary neurotrophic factor (CNTF), cardiotrophin-1 (CT-1) and oncostatin M (OSM). These cytokines share the membrane gp130 as a common signal transducer. Recently, it was demonstrated that IL-6 promotes, whereas LIF inhibits fetal lung branching. Thus, in this study, the effects on fetal lung morphogenesis of the other classical members of the g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 54 publications
(76 reference statements)
1
11
1
Order By: Relevance
“…Herein, it is demonstrated that precise regulation of STAT signaling is necessary for proper fetal lung growth during early development, revealing an unanticipated role of STAT signaling during lung branching morphogenesis. Even though STAT transcription factors have been largely overlooked in lung development, STAT3 has been previously implicated in the regulation of developmental processes [14][15][16][17], namely lung branching [26,27,36], which is consistent with our findings. More importantly, we show that modulation of fetal lung growth can be achieved by conditionally targeting STAT signaling, though the detailed mechanistic interactions are yet to be fully defined.…”
Section: Cellular Physiology and Biochemistrysupporting
confidence: 92%
See 2 more Smart Citations
“…Herein, it is demonstrated that precise regulation of STAT signaling is necessary for proper fetal lung growth during early development, revealing an unanticipated role of STAT signaling during lung branching morphogenesis. Even though STAT transcription factors have been largely overlooked in lung development, STAT3 has been previously implicated in the regulation of developmental processes [14][15][16][17], namely lung branching [26,27,36], which is consistent with our findings. More importantly, we show that modulation of fetal lung growth can be achieved by conditionally targeting STAT signaling, though the detailed mechanistic interactions are yet to be fully defined.…”
Section: Cellular Physiology and Biochemistrysupporting
confidence: 92%
“…Recently, Carraro et al suggested that stabilization of STAT3 RNA expression during the pseudoglandular stage may be important for correct branching morphogenesis [36]. Previous studies have also implicated STAT3 in lung branching morphogenesis [26], and a consistent downstream of STAT3 activation was observed in response to the inhibitory actions of cytokines on fetal lung branching [27].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many factors that regulate fetal lung branching morphogenesis activate signaling pathways that culminate with MAPK, PI3K/Akt and p38 cascades [30,31,40,41,42]. In the present study, ephrin-B1 was found not to modify the phosphorylated levels of these proteins.…”
Section: Discussioncontrasting
confidence: 52%
“…Noteworthy transcripts in these categories/pathways included casein kinase 1, epsilon (CSNK1E) (64), mitogenactivated protein kinase 6 (MAPK6; a.k.a. ERK3) (65), mechanistic target of rapamycin (serine/threonine kinase) (MTOR) (66), oncostatin M (OSM) (67,68), TLR6 (69), mucin 20 (MUC20) (70,71), MAD homolog 1 (SMAD1) (72, 73), (74,75), claudin 3 (CLDN3), CLDN4, CLDN5, CLDN7 (76)(77)(78), and lethal giant larvae homolog 2 (Drosphila) (LLGL2) (79,80).…”
Section: Transcriptomic Analysismentioning
confidence: 99%